PENGARUH KETIDAKPUASAN DAN SIKAP MENGELUH PADA PERILAKU MENGELUH KONSUMEN - Dewi Putri Asih, Ida Ayu Putu; Yudi Setiawan, Putu (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
This study was conducted to determine the effect of discontent and complaining attitude towards consumer complaining behavior at the Grand Santhi Hotel in Denpasar. Design research using the form associative causal (cause and effect). The sample was 100 respondents. The sampling method using purposive sampling method with certain criteria. Data collection techniques used is by distributing questionnaires to customers who are staying at the Grand Santhi Hotel Denpasar. Methods of data analysis using multiple linear  analysis to examine the effect among variables. The study states that the dissatisfaction and complaining attitude is positive and significant effect on the behavior of consumers complained to the Grand Santhi Hotel in Denpasar.
Keywords: Dissatisfaction, Complaining Attitude, Consumer Complaining Behavior.